Money Laundering: Some Facts - Friedrich Schneider; Ursula Windischbauer (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
The term "Money Laundering" originates from the US describing the Mafia's attempt to "launder" illegal money via cash-intensive washing salons, which where controlled by company acquisitions or business formations. Estimated two to five per cent of the global gross domestic product stems from illicit sources. A great deal of the money derives from drug-dealing, with a total revenue of 810 Billion USD in 2003. In 2005 the Austrian Police secured drugs worth 49266800 Euro (drug seizures in terms of street prices), in total 25.892 persons were charged for violation of the Austrian Narcotics Act. Most of all illegal transactions are processed by cash since there is the smallest risk to leave one's mark; nevertheless there exists an obvious tendency to misuse the internet in order to undertake illicit transactions in form of Online- Banking, Cyber money and Electronic Purse.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330